2002
DOI: 10.1074/jbc.m205317200
|View full text |Cite
|
Sign up to set email alerts
|

Decorin Binds to a Narrow Region of the Epidermal Growth Factor (EGF) Receptor, Partially Overlapping but Distinct from the EGF-binding Epitope

Abstract: Decorin, a small leucine-rich proteoglycan, is a key regulator of tumor growth by acting as an antagonist of the epidermal growth factor receptor (EGFR) tyrosine kinase. To search for cell surface receptors interacting with decorin, we generated a decorin/alkaline phosphatase chimeric protein and used it to screen a cDNA library by expression cloning. We identified two strongly reactive clones that encoded either the full-length EGFR or its ectodomain. A physiologically relevant interaction between decorin and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
162
1
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 210 publications
(170 citation statements)
references
References 76 publications
4
162
1
3
Order By: Relevance
“…Another collagen and fibronectin binding leucine-rich protein, decorin, a chondroitin sulfate proteoglycan, shows similar properties to SPARC. Decorin is an antioncogenic and antitumorigenic gene (17,22,33,34). Decorin promotes glioma survival in vitro via the phosphatidylinositol 3-kinase/AKT pathway, as previously reported (18), and glioma survival in vivo in rats as reported by others (35).…”
Section: Discussionmentioning
confidence: 63%
“…Another collagen and fibronectin binding leucine-rich protein, decorin, a chondroitin sulfate proteoglycan, shows similar properties to SPARC. Decorin is an antioncogenic and antitumorigenic gene (17,22,33,34). Decorin promotes glioma survival in vitro via the phosphatidylinositol 3-kinase/AKT pathway, as previously reported (18), and glioma survival in vivo in rats as reported by others (35).…”
Section: Discussionmentioning
confidence: 63%
“…For these experiments the following mutants were used: DCN-Q153, a mutant that contains the N terminus and the first 5 leucine-rich repeats of decorin, and DCN-E180K, a mutant with a point mutation reducing its affinity to collagen type I (21). These two mutants were chosen because previous studies (15) had shown that the N-terminal part of decorin is not involved in binding the EGF receptor but leucine-rich repeat 7, which contains the point mutation (DCN-E180K). Our investigation demonstrated that DCN-Q153 alone was still able to induce Akt phosphorylation ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…How decorin affects differentiation and apoptosis is not completely understood. In tumor cells, decorin binds to the epithelial growth factor (EGF) receptor or ErbB4 and leads to activation of the mitogen-activated kinase (MAPK) pathway, Ca 2ϩ influx, induction of the cyclin-dependent kinase inhibitor, p21, and subsequently to down-regulation of the receptor (13)(14)(15). In endothelial cells decorin affects different pathways.…”
mentioning
confidence: 99%
“…It has been shown that the ECM modulates the activity of growth factors by controlling the proteolytic activation of latent factors, as occurs in the case of transforming growth factor-␤ (37). In addition, ECM molecules, such as decorin, can interact with cell surface receptors so as to prevent binding of the cognate ligand, as occurs in the case of the epidermal growth factor receptor (38). The ECM may also bind growth-promoting factors from the serum for optimal presentation to MSCs.…”
Section: Characterization Of Stepwise Osteogenesis-mimicking Matrices-mentioning
confidence: 99%